Synthesis and Characterization of Random Copolyesters of Aromatic Diols - SULTANA, SAYEEDA; KRISHNAN, SIVARAMA; GUNASEKARAN, S.; VENKATARAMAN, T. (Asian Journal of Chemistry, 2010)
Copolyesters based on adipoyl chloride with aromatic diols were synthesized by solution polycondensation method. The copolyesters were characterised by IR, 1H NMR, UVVisible spectral studies. Solubility was checked in some common organic solvents and they showed better solubility in acetone and dimethyl formamide. The solubility of copolyesters depends on the rigidity of polymer backbone, molecular weight and interaction between polymer and solvent molecules. The random units distributed in the copolyester chain were assigned based on spectral studies.